Dynamic linkages among energy consumption, air pollution, greenhouse gas emissions and agricultural production in Pakistan: sustainable agriculture key to policy success - Qureshi, M. I. (Springer Netherlands, 2016)
This study examines the impact of energy demand, air pollution, fossil fuel energy and greenhouse gas emissions on agricultural production in Pakistan for the period 1980–2013. The study utilized the following variables for agricultural production, i.e., agriculture value added, cotton production, wheat production, rice production and sugarcane production in Pakistan. The study employed generalized method of moments estimator to evaluate different simultaneous equations in relation to environmental factors and agricultural production in a country. The results show that CO2 emissions have a positive and energy sources have a negative impact on agricultural value added. The fossil source of energy has a direct relationship with the cotton and sugarcane production, while CO2 emission has a positive relationship with wheat and sugarcane production. Greenhouse gas emissions badly affected the agricultural production including cotton production, wheat production and rice production. Finally, energy consumption exerts the positive impact on the production of cotton, wheat and rice in Pakistan.